2018
DOI: 10.7324/japs.2018.8207
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Cytotoxic Activities of Endophytic Fungi Isolated from Mangrove Plant Sonneratia alba Sm

Abstract: Endophytic fungi are those that grow intra-or intercellular within the tissues of higher plants without causing a disease. This study aims to evaluated antimicrobial and cytotoxic activities of endophytic fungi from leaf, bark and root of mangrove Sonneratia alba Sm, collected from Bungus, West Sumatra, Indonesia. The isolation of endophytic fungi was done by using direct planting method with sabouraud dextrose agar (SDA) as growth medium. Thirteen isolates fungi strains were obtained from this mangrove. They … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…It was the most predominant endophytic fungi obtained from C. tagal in our study. Prior studies showed that this species is commonly isolated as an endophyte from both terrestrial and marine hosts (Teuscher, 2006;Bhattacharya, 2018;Handayani, 2018;.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was the most predominant endophytic fungi obtained from C. tagal in our study. Prior studies showed that this species is commonly isolated as an endophyte from both terrestrial and marine hosts (Teuscher, 2006;Bhattacharya, 2018;Handayani, 2018;.…”
Section: Discussionmentioning
confidence: 99%
“…Secalonic acid derivative from endophytic A. aculeatus induced apoptosis in triple negative breast cancer cells by reactive oxygen species formation (Farooq, 2020). A. sydowiii from both marine and terrestrial hosts possessed antimicrobial, antioxidant and cytotoxic activity (Handayani, 2018;Bhattacharya, 2018;El-sayed, 2022). The fungal genus Aspergillus from different mangrove hosts is well known as a potential source of various bioactive molecules having antibacterial property (Handayani, 2017;Nurunnabi, 2020;Ramirez, 2020).…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Adanya perbedaan aktivitas antibakteri bisa dikarenakan adanya perbedaan sensitivitas pada bakteri gram positif dan gram negatif yang berhubungan pada ketebalan peptidoglikan yang menjadi penyusun dinding sel bakteri (Handayani et al, 2018). Bakteri gram positif memiliki membrane sel yang mengandung asam teikoat dan petidoglikan yang tebal tapi tidak memiliki membrane luar, sementara pada bakteri gram negatif membrane luar terdapat liposakarida (LPS) yang menyebabkan bakteri lebih resisten pada antibiotik (Subandi, 2012& Panawala, 2017dalam Wulansari et al, 2020.…”
Section: Antibakteriunclassified
“…Various bioactive compounds such as alkaloids, tannins, terpenoids, steroids and phenolic derivatives have potential as mycotoxins, enzymes and antibiotics (Handayani et al, 2018;Pandy et al, 2023). In addition, bioactive compounds from endophytic fungi also show strong antiparasitic and antioxidant activity (Praptiwi et al, 2018;Preuttiporn & Sita, 2019).…”
Section: Introductionmentioning
confidence: 99%